EFEKTIVITAS TEKNIK ENDORPHINE MASSAGE TERHADAP NYERI PERSALINAN PADA IBU BERSALIN KALA I FASE AKTIF - Supriaten Aisyah, Yeki (Journal of Midwifery Tiara Bunda, 2023)
Background :Pain during labor is a manifestation of contractions (shortening) of the uterine muscles. Endhorpine massage is a light touch for relaxation and pain reduction, therefore endhorpine massage can be done for women in labor who experience pain. Reseach Purposes : This study aims to determine the effectiveness of Endorphine Massage on labor pain in women in the first active stage of labor at PMB Sri Mulyati Tangerang City. Research Method : The research method used was quasi-experimental with a twogroup pre and post test design. Samples were taken using the sampling technique is total sampling, namely as many as 13 respondents. The instruments in this studyused the Endorphine Massage Standard Operating Procedure (SOP) sheet and the Numeric Rating Scale (NRS) which consists of a scale of 0-10 to describe the intensity of pain experienced by respondents. Research Results : The results showed that there was a significant difference in the pain score of the respondents before and after being given Endorphine Massage with the t test obtained p-value = 0.000. Conclusion : Endorphine massage techniques are effective in reducing pain in labor during the first active phase at PMB Sri Mulyati Tangerang City.The English abstract contains the introduction, objectives, methods, results and conclusions, written in one paragraph with a maximum of 200 words. Abstracts must be as short as possible, accurate and clear and describe the research you are doing and confirm the results of the research/development. Written with Arial font format, 11 pt, 1 space, italic, and right and left alignment